Análisis socio-técnico sobre el uso comunicacional de los teléfonos inteligentes en los jóvenes universitarios, caso: Universidad Politécnica Salesiana – Campus El Girón - Campos Gaibor, Adrián Francisco (2018)
The objective of this article is to carry out a socio-technical communication analysis on the use of mobile technologies, in university students and how it determines the way of communicating and interacting in the life of university students at a personal, academic and professional level, for which required the application of a survey, with the purpose of raising the divisions and oppositions between technology and society of university students. This research maintained a documentary bibliographic modality. As the present research work shows, it is clear that a higher percentage of university students use Smartphone technology in their academic activities, social, work, personal, family relationships, among others. The use of the cell phone in young people shows a tendency to rise, as well, the phenomenon of technological dependence shows a boom. The culture of use of digital technology updates of applications and cellular innovations, order, technical are daily, in the same line, the socio-cultural phenomenon of young people has been an evident phenomenon demonstrated in the dynamics of social relations and new ways of perceiving personal and social coexistence. The era of democratization in information and technology in communication modes have as main actors young university students, who are currently setting new directions in the socio-technical discourse of a 21st century society.